Can pesticides, copper and seasonal water temperature explain the seagrass Zostera noltei decline in the Arcachon bay?. (September 2018) - Gamain, Perrine; Feurtet-Mazel, Agnès; Maury-Brachet, Régine; Auby, Isabelle; Pierron, Fabien; Belles, Angel; Budzinski, Hélène; Daffe, Guillemine; Gonzalez, Patrice
Abstract: Dwarf eelgrasses ( Zostera noltei ) populations have decreased since 2005 in Arcachon Bay (southwest France). Various stressors have been pointed out, however the role of xenobiotics like pesticides or copper (Cu) and of parameters like water temperature warming have not yet been explored. To determine their impact, Z. noltei individuals were collected in a pollution-free site and transferred to the laboratory in seawater microcosms. This dwarf eelgrass was exposed to a pesticide cocktail and copper, alone or simultaneously, at temperatures (10 °C, 20 °C, 28 °C) representative of different seasons. After a two-week contamination, leaf growth, leaf bioaccumulation of Cu, and differential expression of target genes were studied. Eelgrasses bioaccumulated Cu regardless of the temperature, with reduced efficiency in the presence of the Cu and pesticide cocktail at the two higher temperatures. High temperature also exacerbated the effect of contaminants, leading to growth inhibition and differential gene expression. Mitochondrial activity was strongly impacted and higher mortality rates occurred. Experimental results have been confirmed during field survey. This is the first report on the impacts on Z. noltei of pesticides and Cu associate to temperature. Highlights: Zostera noltei decline in the Arcachon Bay (southwest France) Molecular effects of Copper and Pesticides cocktail used alone or mixed Cu and Pesticides decreased the mitochondrial metabolism and photosynthesis